Penatalaksanaan Chest Physiotherapy Pada Kondisi Bronkitis Akut di RS Paru Dr. Ario Wirawan Salatiga - Mardatila, Antina Ria; , Isnaini Herawati, S.Fis, S.Pd, M.Sc (2016)
Background: Bronchitis is inflamation mucous at broncus. This inflamation cused the surface of broncus become swelling until shoot of respiration is tighten. Acute bronchitis within 24 until 48 hours. The symptom include continue a cough with sputum, chest pain, have difficulty breathing and usually with fever. And for superintend that problem, the modality is chest physiotherapy with cough exercise and thoracic expantion exercise. Objective: To know influence of chest physiotherapy with cough exercise and thoracic expantion exercise for decrease sputum, chest pain, level of crowded and increase wide of thoracic expantion in the case of acute bronchitis. Results: After treatment for 4 times the obtained results on the assessment of level of crowded with Borg scale: T1: 5 become T4: 2. This is indicate that level of crowded is decrease. At inspection of chest pain with VAS (cm), the result is decrease with output T1: quite pain (0), movement pain (3,4), pressure pain (2,5) become T4: quite pain (0), movement pain (1,9), pressure pain (1,5). When auskultation for know sputum, the result is decrease with output T1: 100% become T4: 15%. And for wide thoracic expantion with meterline, after treatment for 4 times is increase as many as 1 cm at axis axilla, 4 cm at axis ICS 4, and 5,4 cm at axis processus xypoideus. Conclusion: Management chest physiotherapy with thoracic expantion exercise in the case of acute bronchitis founding result be present decrease the level of crowded with borg scale, decrease chest pain with VAS, decrease sputum and increase wide thoracic expantion with meterline. Keywords: Acute bronchitis, chest physiotherapy, thoracic expantion exercise, borg scale, VAS (Visual Analogue Scale), meterline, cough exercise.